2020
DOI: 10.3390/medicina56060260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cesarean Section and Vaginal Delivery on Abdominal Muscles and Fasciae

Abstract: Background and objectives: Possible disorders after delivery may interfere with the quality of life. The aim of this study was to ascertain whether abdominal muscles and fasciae differ in women depending on whether they experienced transverse cesarean section (CS) or vaginal delivery (VA) in comparison with healthy nulliparous (NU). Materials and methods: The thicknesses of abdominal muscles and fasciae were evaluated by ultrasound in 13 CS, 10 VA, and 13 NU women (we examined rectus abdominis (RA); external o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
19
0
1
Order By: Relevance
“…14 Abdominal fascial thickness values are reported in three other studies. 12,33,39 The thickness values reported in the present study are very similar to those reported in the reliability study published by Pirri et al 33 However, their thickness measurements were based only on one participant. It would have been interesting to know whether the similarity would have continued if the data had been collected on a larger sample.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…14 Abdominal fascial thickness values are reported in three other studies. 12,33,39 The thickness values reported in the present study are very similar to those reported in the reliability study published by Pirri et al 33 However, their thickness measurements were based only on one participant. It would have been interesting to know whether the similarity would have continued if the data had been collected on a larger sample.…”
Section: Discussionsupporting
confidence: 89%
“…It would have been interesting to know whether the similarity would have continued if the data had been collected on a larger sample. The current results cannot be compared to the two other studies 12,39 due to differences in methods. Neither study reported individual epimysial fascia thicknesses, but both reported the sum of all fascia thickness measurements.…”
Section: Discussionmentioning
confidence: 79%
“…In 2016, Ramin et al [ 51 ] published an extensive anatomical analysis of the so-called “fascial continuum” within the area of the pelvis and torso [ 51 ]. If, from a fascial point of view, the abdominal muscles are synergistically connected with the thoracolumbar fascia and the pelvic floor muscles [ 52 ], what effect may an incorrect posture have on their functional status and the formation of pelvic floor dysfunctions?…”
Section: Discussionmentioning
confidence: 99%
“…A 2015 literature review [ 51 ] on the anatomical, myofascial relationships between the pelvic floor, abdominal muscles, and back muscles formed an important theoretical basis for this project, referring to the multitude of fascial functions [ 52 ]. Based on the characteristic features of fasciae such as the transmission of force, the coordination of movements, stability, and proprioceptive communications throughout the body [ 52 ], it seems that any dysfunction along the myofascial chain may cause the overcompensation and dysfunction of other associated muscles [ 34 ]. In the case of PFMs, a persistent lack of muscle relaxation and/or heightened muscular activity may lead to involuntary muscle contraction, which in turn can lead to pelvic pain syndrome, involving taut bands and trigger points [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correlations have been found between body mass and fascia thickness (τ = 0.45–0.75, p < 0.05) as well as between flexibility and fascia thickness (τ = 0.38–0.42, p < 0.05). We reported in one of our previous works that the thickness of the rectus sheath was significantly thicker in women who had undergone a caesarean section with respect to those who had undergone a vaginal delivery and/or healthy nulliparous women [ 25 ].…”
Section: Thickness Of the Deep/muscular Fasciaementioning
confidence: 99%